2016
DOI: 10.1017/s0007114514004243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal and/or postnatal supplementation with iron, PUFA or folic acid on neurodevelopment: update

Abstract: Neurodevelopment has been linked, among other factors, to maternal and early infant diets. The objective of this review, which is part of the NUTRIMENTHE research project 'The effect of diet on the mental performance of children' (www.nutrimenthe.com), was to update current evidence on the effects of nutritional interventions such as iron, folic acid or n-3 long-chain polyunsaturated fatty acid (LCPUFA) supplementation during pregnancy and/or in early life on the mental performance and psychomotor development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Nevertheless, a sufficient supply of LC-PUFAs is likely to be of importance upon weaning from the breast milk 21 The published human studies provide contradictory data regarding maternal diet or fatty acid status during pregnancy on child development even though variable methods have been used to evaluate this phenomenon (reviewed in ref. 22 ). Generally, an increase in n-3 fatty acids either through consumption of relevant food sources, mainly fish or supplement use, has been considered as being beneficial in view of the importance of n-3 LC-PUFAs as structural and functional components in brain and retina 23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, a sufficient supply of LC-PUFAs is likely to be of importance upon weaning from the breast milk 21 The published human studies provide contradictory data regarding maternal diet or fatty acid status during pregnancy on child development even though variable methods have been used to evaluate this phenomenon (reviewed in ref. 22 ). Generally, an increase in n-3 fatty acids either through consumption of relevant food sources, mainly fish or supplement use, has been considered as being beneficial in view of the importance of n-3 LC-PUFAs as structural and functional components in brain and retina 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, despite intensive research in the area of fatty acid supplementation, no conclusive evidence exists thus far regarding child neurodevelopment or cognition and visual outcomes (reviewed in ref. 22,30 ), the benefits mainly manifested in preterm born infants 31 . In agreement with our study, although in that other publication, the child's development was evaluated by a psychological test, Mendez and co-workers 32 found that maternal fish consumption in excess of two to three times per week was associated with higher test scores when the child was four years old.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although aspects of language are captured by various assessments in a many of these RCTs, these are often overlooked as secondary or exploratory outcomes, and hence there is yet to be a review where language outcomes are collated and considered as a whole [ 19 , 20 , 21 , 22 , 23 , 40 , 41 ]. Furthermore, whilst adequate DHA is likely to be important throughout the whole of the first 1000 days, two reviews to date have attempted to synthesize [ 42 ] or provide at least a very brief overview [ 43 ] of the evidence across this period and language was not reported in either.…”
Section: Introductionmentioning
confidence: 99%